The large scale bioinformatics analysis of auxiliary activity family 9 enzymes - Moses, Vuyani (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Biofuels have been proposed to be a suitable replacement to the already depleting fossil fuels. The complex structures of plant biomasses present a challenge the production of biofuels due to recalcitrance. The complex cellulose structure and hydrogen bonding between repeat units of cellulose is believed to be a major contributor to the recalcitrance of cellulose. Fungal organisms come equipped with various oxidative enzymes involved in degradation of plant biomass. The exact mechanism of cellulose degradation remains elusive. The GH61 is a group of proteins which are PMOs. GH61 sequences where previously described as endoglucanases due to weak endoglucanase activity. These enzymes were later found not possess any enzyme activity of their own however they could enhance the activity of other cellulose degrading enzymes. As a result reclassification of these enzymes as AA9 has been implemented. AA9 proteins have been reported to share structural homology with the bacterial AA10 group of enzymes. Based on cleavage products that are produced when AA9 proteins interact with cellulose, AA9 proteins have been grouped into three types. To date the exact mechanism and the sequence and structural basis for differentiating between the various AA9 types remains unknown. Using various bionformatic techniques sequence and structural elements were identified for distinguishing between the AA9 types. A large dataset of sequences was obtained from the Pfam database from UNIPROT entries. Due to high divergence of AA9 sequences, a smaller dataset with the more divergent sequences removed was created. The inclusion of the reference sequences to the data set was done to observe which sequences belong to a certain type. Phylogenetic analysis was able to group AA9 proteins into three distinct groups. MSA and motif analysis revealed that the N-Terminus of these proteins is mostly responsible for type specificity. Structural analysis of AA9 PDB structures and homology models allowed the effect of physicochemical properties to be gauged structurally. The presence of 310 helices and aromatic residues the surface of AA9 sequences is an observation which still warrants further investigation.
Keywords: Bioinformatics -- Analysis; Cellulose -- Biodegradation; Biomass energy